Microbial strategies for bio-transforming food waste into resources - Sharma, Poonam; Gaur, Vivek Kumar; Kim, Sang-Hyoun; Pandey, Ashok (Bioresource technology, 2020)
With the changing life-style and rapid urbanization of global population, there is increased generation of food waste from various industrial, agricultural, and household sources. According to Food and Agriculture Organization (FAO), almost one-third of the total food produced annually is wasted. This poses serious concern as not only there is loss of rich resources; their disposal in environment causes concern too. Food waste is rich in organic, thus traditional approaches of land-filling and incineration could cause severe environmental and human health hazard by generating toxic gases. Thus, employing biological methods for the treatment of such waste offers a sustainable way for valorization. This review comprehensively discusses state-of-art knowledge about various sources of food waste generation, their utilization, and valorization by exploiting microorganisms. The use of microorganisms either aerobically or anaerobically could be a sustainable and eco-friendly solution for food waste management by generating biofuels, electrical energy, biosurfactants, bioplastics, biofertilizers, etc.